Mapping Interstate Territorial Conflict: A New Data Set and Applications. (August 2017) - Schultz, Kenneth A.
This article describes a new data set consisting of precise digital maps of regions that were the subject of interstate territorial disputes in the period 1947 to 2000. Each dispute identified by Huth and Allee is rendered as a polygon corresponding to the area subject to overlapping claims. After describing the data collection procedures and presenting some descriptive statistics, this article develops three novel results that demonstrate the potential of geospatial data to advance our understanding of the causes and consequences of territorial conflict. In particular, I use the data to (1) show how different measurements of the geographic extent of disputes can help unpack the mechanisms through which they dampen international trade, (2) cast doubt on the role of oil deposits in fueling territorial conflict by analyzing the relationship at a finer level of spatial resolution than previously possible, and (3) examine the harmful legacy of territorial conflict on local development in formerly contested regions along the El Salvador-Honduras border.